The Work of SAVI Model, Direct Learning Model and Learning Motivation to Increase Learning Outcome for Elementary Students - Putri, Della Malaya; Leksono, Ibut Priono; Cholid, Abd. (International Journal of Educational Technology and Learning, 2019)
It is found that most students from rural areas facing learning difficulties. Based on these problems, researchers are encouraged to examine the student learning outcomes using SAVI learning models and direct learning models, and want to see the differences in learning outcomes between students who have high and low learning motivation. The applied learning model is adapted to the characteristics of students by using concrete objects as media in learning activities, as well as in experimental activities. The models are applied to the students of State Elementary School (SDN) Sidoharjo 1 and State Elementary School (SDN) Pagerluyung 1 Mojokerto grade 6 related to science learning. The results of the study show that there are differences in learning outcomes between students who use the SAVI learning model and the Direct learning model and are combined with high or low student learning motivation. The application of the SAVI learning model with high learning motivation resulted in an average value of 87.581, while the average value of the results of the application of the direct learning model which was also accompanied by high learning motivation reached 84.643. The use of the SAVI model shows higher learning outcomes than the direct learning model.